Effect of Ordinary Portland Cement (OPC) and Blended Hydraulic Cement (BHC) on the Behaviour of Self-Compacting Concrete - Deshabandu, D.S.; Ariyarathne, K.C.; Athapaththu, M.A.A.D.O.; Janarthanan, B. (The Institution of Engineers, Sri Lanka, 2022)
Self-compacting concrete (SCC) is a special type of concrete that flows under its own weight while enhancing the compressive strength and durability compared to conventional concrete. This is an effort to present the possibility of using Blended Hydraulic Cement (BHC) instead of ordinary Portland cement (OPC) in SCC production. In order to achieve the required workability and basic mechanical properties, 10 control mixes of SCC with OPC were prepared using the coarse aggregate size of 5 mm – 14 mm. Each mix was cast using 100% OPC and 100% BHC separately. Fresh properties of the SCC were tested by using slump flow, V-funnel, L-box and J-ring test according to the EFNARC guideline. 9-cubes and 6-cylindrical specimens were cast per mix to determine the compressive strength at the 7th, 28th and 56th days. Test results illustrate that the workability properties of fresh concrete mix are moderately good using both cement types. Most mixes show higher 28th and 56th-day compressive strengths for SCC mix made of BHC than OPC compared with 7th-day compressive strength variation. Fly ash in BHC contributes later strength gaining of SCC in this study. Thus, the experimental investigation indicates the suitable mix designs used in the current construction industry.
Keywords: Compressive strength; Fly ash; Blended hydraulic cement; Self-compacting concrete; Superplasticizer